2021
DOI: 10.1080/03019233.2020.1852843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooling uniformity on the internal reduction efficiency of a slab

Abstract: Cooling uniformity has a great influence on slab solidification. To study its effect on the internal reduction efficiency, a thermo-mechanical coupling slab solidification model was studied and an internal reduction efficiency calculation model was established. Numerical simulation was performed with ProCAST software and verified by a pin shooting test. The results showed that under uniform cooling, when the reduction amount was more than 3 mm, the internal reduction efficiency was 38-41%, and under non-unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The formation mechanisms of center segregation have been investigated by many researchers. [3][4][5][6][7] The low superheat casting, [8][9][10] electromagnetic stirring, [11][12][13][14] and mechanical reduction [15][16][17][18] were proposed to reduce the center segregation defect in the continuous casting. However, the influence of RGD [19,20] on solute redistribution is less studied, even though it is commonly observed in the continuous caster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation mechanisms of center segregation have been investigated by many researchers. [3][4][5][6][7] The low superheat casting, [8][9][10] electromagnetic stirring, [11][12][13][14] and mechanical reduction [15][16][17][18] were proposed to reduce the center segregation defect in the continuous casting. However, the influence of RGD [19,20] on solute redistribution is less studied, even though it is commonly observed in the continuous caster.…”
Section: Introductionmentioning
confidence: 99%
“…Domitner et al [ 15 ] indicated that the mechanical reduction zone should cover the end position of shell bulging, where the segregation can be reduced. Both conducted experiment and simulation, Li et al [ 16 ] found the reduction efficiency was improved clearly with the uniform cooling, and the center segregation of the slab 1/4 width was reduced with a larger reduction amount. Bleck et al [ 17 ] indicated that the reduction position is an important factor for slab center segregation improvement.…”
Section: Introductionmentioning
confidence: 99%